THE EVOLUTION OF REGULATORY FRAMEWORKS IN THE FINTECH INDUSTRY: NAVIGATING COMPLIANCE IN A TECHNOLOGICALLY ADVANCED WORLD - Preethi Ravisankar, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The evolution of regulatory frameworks in the FinTech industry presents both opportunities and challenges as organizations navigate an increasingly complex compliance landscape. From digital payments to decentralized finance, FinTech's transformative impact on global financial services necessitates robust regulatory oversight while maintaining innovation. The landscape spans major jurisdictions including the European Union's comprehensive approach, the United States' fragmented structure, and the Asia Pacific region's diverse regulatory environment. As organizations leverage advanced technologies like machine learning, natural language processing, and big data analytics for compliance, a shift toward "compliance by design" emerges as a crucial strategy. The integration of automated workflows, continuous risk assessment, and privacy-first architectures demonstrates the industry's commitment to balancing regulatory requirements with technological advancement.